Pulling men into the care economy: The case of Canadian firefighters. (June 2015) - Braedley, Susan
Professional urban fire services across the United States and Canada are now engaged in care work, as a significant aspect of their work as emergency medical first responders. Given that the historically resilient world-wide unequal gendered division of labour continues to assign care to women, and to subaltern women in particular, the engagement of this primarily white, male labour force bears examination. In Canada, the late 1990s saw fire responses to 'medical' emergencies increase dramatically to become the dominant call category for fire services, as part of a tiered emergency response. Further, these responses are seldom to heart attack, stroke or catastrophic events for which firefighters are trained, but instead are responses to more predictable and recurring issues imperiling the health and well-being of people with chronic illnesses, disability or frailty. Using data collected from research in four Canadian cities, this article explains how fire services have been pulled into emergency care concurrent with health care and social services re-structuring and what this move tells us about re-structuring in terms of the fragility of the care economy and masculinized public sector work.